Process analysis and kinetic study on the reduction of iron ore powder by H2-CO mixtures using a fluidized bed-mass spectrometry coupling technique - Wang Shulin; Wang Linwei; Zhang Jiehan; Li Shiyuan (Fuel, 2026)

Study on pig cough recognition and spatial localization based on multi-source noise separation - Yue Cao; Zhe Yin; Yongpeng Duan; Penghui Li; Jing Zeng; Linwei Li; Guangying Hu; Zhenyu Liu (Computers and Electronics in Agriculture, 2026)

Influence of soil types with different soil-forming process on the qualitative and quantitative detection of microplastics by near-infrared spectroscopy - Linwei Cai; Zengling Yang; Zhuolin Shi; Xintong Zhang; Jinzhao Li; Lujia Han (Journal of Environmental Sciences, 2026)

Injectable enzyme-triggered conductive hydrogel for restoring electrical homogeneity and functional recovery in myocardial infarction - Shun Xie; Fengjiao Deng; Ying Lu; Min Li; Shen Shen; Qin Wang; Weidong Li; Linwei Chen (Chemical Engineering Journal, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Controlling effect of the karst hydrogeological structure on karst collapse: a case study of the Chaoyang Tunnel, Guizhou - Lei Zhang; Xiqiong Xiang; Linwei Li; Wenjun Wang; Xiangquan Li (Carbonates and Evaporites, 2026)

Integrative genomic analyses reveal genetic structuring and cyto-nuclear incongruences within the Corbicula species complex in China - Yangxin Tang; Linwei Liu; Jie Pi; Xinhua Liu; Jianguo Xiang; Joong-Ki Park; Neil E. Coughlan; Deliang Li (Molecular Phylogenetics and Evolution, 2026)

Early-Life Stages Amplify the Ecotoxicological Vulnerability of Freshwater Gastropods to the Agricultural Fungicide Prochloraz - Jiyuan Wang; Hairun Li; Jialu Xu; Yanlai Yao; Linwei Chen; Ruke Wang; Yuqing Shao; Lu Yang; Xiaofen Zhang; Xiaodong Yao; Lijun Lin; Hongyu Li (Journal of Hazardous Materials, 2026)

Natural radionuclides in atmospheric deposition and their responses to sandstorm events: A case study in Lanzhou - Linwei Li; Qiangqiang Zhong; Penggao Fang; Qiugui Wang; Wenyi Guo (Journal of Environmental Radioactivity, 2026)

Integrated hydrogen system analysis across the resource-environment-economy nexus: a case study of China - Maximilian Arras; Anne Yingqiu Liang; Yuning Fu; Zheng Li; Linwei Ma (Journal of Industrial Ecology, 2026)

Two unusual stereoisomeric dammarane-type triterpenoid saponins from the leaves of Panax japonicus (T. Nees) C. A. Mey - Yezi Ma; Linwei Dan; Wei Wang; Yuze Li; Xiaomei Song; Hao Fan; Dongdong Zhang (Natural Product Research, 2026)

Influence of soil types defined by soil genesis on the qualitative and quantitative detection of microplastics in soil by mid-infrared spectroscopy - Linwei Cai; Chunxu Wan; Zengling Yang; Zhuolin Shi; Xintong Zhang; Jinzhao Li; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Failure pattern of ring-shaped leakage-induced ground collapse under varying pipeline fracture spacings in red clay areas: Insights from semiphysical modeling - Kai Wang; Linwei Li; Xiqiong Xiang; Yiping Wu; Fasheng Miao (Engineering Geology, 2026)

SAF-YOLO: Super-resolution augmented detection model with visual state space enhancement for safflower filament picking - Duan Mengyu; Wang Xiaorong; Qiu Linwei; Li Menghao; Chen Jinrong; He Liang (Precision Agriculture, 2026)

Virus-inclusive microbial network relationships align with the stress gradient hypothesis in saline-alkali agroecosystems - Fang Li; Linwei Wu; Changlin Xu; Shuwen Guo; Jinhua Zhao; Yi Wang; Peipei Li; Biao Zhu (Soil Biology and Biochemistry, 2026)

Heteroaptamer recognition mediated strand displacement amplification for efficient electrochemical analysis of beta-2-microglobulin in breast milk - Yaqin Tang; Tingting He; Linwei Pan; Yanni Wang; Xiaolong Li; Xia Zhao; Daxiu Li; Baoting Dou (Food Chemistry, 2026)

Salicylic acid-mediated biosynthesis of anti-oomycete diterpenoids in Euphorbia lathyris L. suspension cells - Pirui Li; Xi Sun; Guodong Zhang; Bi Wang; Chenxing Xiao; Mei Tian; Shu Xu; Hui Liu; Xu Feng; Linwei Li; Wanli Zhao; Yu Chen (Plant Cell Reports, 2026)

lncRNA DLGAP1-AS2 Modulates the TGF-β/Smad Signaling Pathway to Regulate Epithelial-Mesenchymal Transition in Renal Cell Carcinoma - Honghao Cao; Junlong Zhu; Ling Zhang; Linwei Li; Langchuan Ma; Chenchen Xie (Biochemical Genetics, 2026)

Hydrogen integration in China’s aviation sector: Techno-economic optimization for flight network decarbonization - Maximilian Arras; Falk Zimmer; Alexander Rau; Wubin Yan; Zheng Li; Linwei Ma (Resources, Conservation and Recycling, 2026)

Phyllosphere microbiome-physicochemical dynamics shape nitrogen resorption efficiency divergence during leaf senescence in subtropical forests of southern China - Bing Xue; Guoping Tang; Zhongkai Ren; Linwei Zeng; Xiaobin Li; Yuqi Li; Nan Jiang (Forest Ecology and Management, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Effect of H2O(g) on the hydrogen reduction of iron ore in fluidized bed - Shiyi Ren; Linwei Wang; Jiehan Zhang; Shiyuan Li (Fuel, 2026)

Two key triggers and their mechanisms of the spring rainy season onset over southern China - Kexu Zhu; Wen Chen; Peng Hu; Linwei Jiang; Ruowen Yang; Lixuan Huang; Qingyu Cai; Yongmao Peng; Jingnan Li; Lu Gao; Qi Yan; Yehong Luo (Atmospheric Research, 2026)

Preparation of high-specificity monoclonal antibody based on rational hapten design and development of immunoassay for accurate detection of dexamethasone in milk and animal tissues - Hongfei Yang; Liangni Qin; Jiaxu Xiao; Xiaoming Pan; Shiyun Han; Linwei Zhang; Jixiang Liang; Yu Si; Hao Wen; Long Li; Xingyu Wang; Xiaojuan Zhang; et al. (Food Bioscience, 2025)

Localized surface plasmon enhancement strategy with synergistic dual-mechanism fluorescence quenching for developing highly sensitive lateral flow immunoassays - Mingyue Ding; Hao Wen; Long Li; Yu Si; Jixiang Liang; Shixiang Wu; Linwei Zhang; Hongfei Yang; Shiyun Han; Xiaoming Pan; Yiting Wang; Jiacan Wang; et al. (Chemical Engineering Journal, 2025)

The role of TLR4/NF-kB signaling axis in pneumonia: from molecular mechanisms to regulation by phytochemicals - Jun Yin; Jianxiang Huang; Ping Zhou; Linwei Li; Qin Zheng; Hong Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Biobased carbon quantum dots: An emerging nano-enabled paradigm for pesticide removal and sustainable plant protection - Usman Arshad; Dan Chen; Haichao Cao; Chao Feng; Linwei Liu; Muhammad Amjad Ali; Zhang Wanhong; Yishan Li; Lijun Jiang; Jinguang Yang (Science of The Total Environment, 2025)

Identification of the exposure pathway to micro-scaled biogenic silica debris via diet and its potential effect in promoting esophageal squamous cell carcinoma - Shenxi Deng; Yi Yang; Erica Celeste Conway; Si Li; Cha Huang; Zigu Chen; Haisheng Wu; Yuan He; Shuzhe Xie; Aifang Ji; Jingyan Zhang; Yansheng Gu; et al. (Journal of Hazardous Materials, 2025)

Resveratrol-integrated Se-chitosan nanogel for protein corona-mediated blood-brain barrier traversing and anti-inflammatory treatment for Parkinson's disease - Yuan Cao; Linwei Zhao; Qing Li; Bo Song; Yuming Xu; Lin Jiang; Shaohua Li (Chemical Engineering Journal, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Improvement of soil quality, microbial community structure and function with the application of microbial agent in continuous cropping of Pinellia ternata - Rong Deng; Yuan Zhao; Lin Chen; Siqi Li; Linwei Jiang; Xiaomei Wang; Tao Yang; Xueping Tian; Jun Huang (Plant and Soil, 2025)

Observational climatology and interannual variability of the spring rainy season onset over southern China: Objective definition and influence from tropical Pacific Ocean - Kexu Zhu; Wen Chen; Peng Hu; Yehong Luo; Ruowen Yang; Linwei Jiang; Qingyu Cai; Lu Gao; Jingnan Li; Yongmao Peng; Changhao Wu; Ziqi Niu (Atmospheric Research, 2025)

Spermatogenesis and ultrastructure of the spermatozoa at three ploidy levels in the bivalve species, Corbicula fluminea - Jie Pi; Yangxin Tang; Ying Fu; Xu Wang; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Tissue and Cell, 2025)

Converting plastic waste into wood-plastic composite products – A practical environmental impacts assessment using primary data - Liancheng Li; Jian Zuo; Ruidong Chang; Linwei Du (Resources, Conservation and Recycling, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

Genetic advancements and future directions in ruminant livestock breeding: from reference genomes to multiomics innovations - Songsong Xu; Zhanerke Akhatayeva; Jiaxin Liu; Xueyan Feng; Yi Yu; Bouabid Badaoui; Ali Esmailizadeh; Juha Kantanen; Marcel Amills; Johannes A. Lenstra; Anna M. Johansson; David W. Coltman; et al. (Science China Life Sciences, 2025)

Probabilistic Assessment of Constitutive Model Parameters: Insight from a Statistical Damage Constitutive Model and a Simple Critical State Hypoplastic Model - Yang Xue; Fasheng Miao; Yiping Wu; Linwei Li; Daniel Dias; Yang Tang (Journal of Earth Science, 2025)

Mechanism and kinetics of direct reduction reaction between H2/CO and hematite powder in a fluidized bed - Jiehan Zhang; Linwei Wang; Chuanhao Wang; Shiyi Ren; Shiyuan Li (Chemical Engineering Journal, 2025)

Temperature drives reproductive activity in a rare trioecy population of Corbicula clams - Jie Pi; Yangxin Tang; Neil E. Coughlan; Linwei Liu; Xu Wang; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2025)

Combined effects of ammonia nitrogen, nitrite, salinity, and temperature negatively impact the growth, survival, physiological, and biochemical parameters, and hepatopancreatic structure of Litopenaeus vannamei - Xuenan Li; Linwei Wang; Xilin Dai (Aquaculture, 2025)

In vitro simulated digestive properties of Monascus vinegar melanoidins, and cytoprotective functions on Caco-2 cells - Kuaitian Wang; Yuwei Li; Xiaojia Bian; Chen Wang; Donghui Geng; Linwei Yu; Yongqiang Cheng; Hongbin Chen; Ning Tang (Food Research International, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

Enhancing high-temperature energy storage properties of polyetherimide dielectrics by constructing hierarchical Coulomb blockade layers of gold nanoparticles - Shuimiao Xia; Li Lei; Linwei Zhu; Qingyang Tang; Zengliang Ren; Davoud Dastan; Zhicheng Shi (Chemical Engineering Journal, 2025)

What influences the on-site recycling behaviour of C&D plastic waste in Australia? An action determination model approach - Liancheng Li; Jian Zuo; Linwei Du; Ruidong Chang (Journal of Environmental Management, 2024)

Lignocellulose degradation and temperature adaptation mechanisms during composting of mushroom residue and wood chips at low temperature with inoculation of psychrotolerant microbial agent - Xueping Tian; Xiaomeng Qin; Xiaojun Jia; Qingyang Lyu; Siqi Li; Linwei Jiang; Lin Chen; Zhiying Yan; Jun Huang (Environmental Pollution, 2024)

Probabilistic back analysis of reservoir landslide considering hydro-mechanical coupled observations - Yang Xue; Fasheng Miao; Jingze Li; Yiping Wu; Linwei Li (Computers and Geotechnics, 2024)

Records of Fukushima accident-derived cesium-137 in the Chukchi Sea sediment: Implication for a new time marker? - Xu Ren; Jinlong Wang; Gi Hoon Hong; Linwei Li; Qiangqiang Zhong; Dekun Huang; Tao Yu; Jinzhou Du (Science China Earth Sciences, 2024)

Baseline sensitivity and resistance risk of Sclerotinia sclerotiorum to glabridin and the possible anti-fungal mechanism - Shu Xu; Chenyang Liu; Jin Chen; Linwei Li; Siwei Qiao; Mei Tian; Qian Zhou; Xingzeng Zhao; Yu Chen; Fei Liu; Xu Feng (Pesticide Biochemistry and Physiology, 2024)

Design of 3D printing superhydrophilic pyramid-shaped porous materials for oil-in-water emulsion separation and visualization of separation mechanism - Liangliang Shen; Yu yang; Hongyin Li; Shilun Shi; Linwei Shi; Zhiying Ren (Chemical Engineering Journal, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Extraction and purification, pharmacological action, synthesis and product development of salidroside: a review - Yaxiao Liu; Linwei Dan; Jiamei Tang; Zitong Yin; Longzhu Yang; Dongdong Zhang; Xiaomei Song; Wei Wang; Yuze Li (Medicinal Chemistry Research, 2024)

Niche similarity accompanying COI genetic differentiations in asexual and sexual Corbicula lineages within East and Southeast Asia - Yangxin Tang; Jie Pi; Neil E. Coughlan; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2024)

Targeted discovery of unusual diterpenoids with anti-fungal activity from the root of Euphorbia lathyris - Yiwei Wang; Shu Xu; Guodong Zhang; Pirui Li; Chenyang Liu; Jiarui Zhou; Xu Feng; Linwei Li; Yu Chen (Phytochemistry, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Development of time-resolved fluorescence immunochromatography and ic-ELISA based on monoclonal antibodies specifically recognizing fumonisin B1 - Xiaoming Pan; Yalin Yang; Huaming Li; Jiaxu Xiao; Linwei Zhang; Shixiang Wu; Hao Wen; Bencheng Wu; Dapeng Peng (Food Bioscience, 2024)

A preliminary assessment of CO2 capture, transport, and storage network for China's steel sector - Yuancheng Lin; Tubagus Aryandi Gunawan; Cecelia Isaac; Hongxi Luo; Fangwei Cheng; Eric D. Larson; Chris Greig; Linwei Ma; Zheng Li (Journal of Cleaner Production, 2024)

Macro and micro connections for slip zone soils of landslide under wetting–drying cycles in the Three Gorges Reservoir area - Fasheng Miao; Fancheng Zhao; Yiping Wu; Linwei Li; Yanming Ding; Jiajia Meng (Landslides, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

Research on the Penetration Coefficient During the Rock Drilling Process by Cyclic Impact - Jinguang Li; Yu Liu; Linwei Wang; Yumeng Sun; Xin Li; Junjie Wang (Rock Mechanics and Rock Engineering, 2024)

Effects of acid mine drainage on photochemical and biological degradation of dissolved organic matter in karst river water - Linwei Li; Xingxing Cao; Chujie Bu; Pan Wu; Biao Tian; Yongheng Dai; Yeye Ren (Journal of Environmental Sciences, 2024)

Methane emission and influencing factors of China's oil and natural gas sector in 2020–2060: A source level analysis - Shuo Sun; Linwei Ma; Zheng Li (Science of The Total Environment, 2023)

Spatio-temporal characterization of dissolved organic matter in karst rivers disturbed by acid mine drainage and its correlation with metal ions - Linwei Li; Xingxing Cao; Pan Wu; Chujie Bu; Yeye Ren; Kai Li (Science of The Total Environment, 2023)

Coordinating energy and material efficiency strategies for decarbonizing China's iron and steel sector - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

Understanding the drivers of CO2 growth in China's iron and steel sector: An integrated analysis of the energy–material–economy nexus - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

A large-scale climate-aware satellite image dataset for domain adaptive land-cover semantic segmentation - Songlin Liu; Linwei Chen; Li Zhang; Jun Hu; Ying Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

How will China's steel demand develop under the investment-driven patterns? Integrating extended input-output model with dynamic steel flow analysis - Yuancheng Lin; Linwei Ma; Zheng Li; Weidou Ni (Journal of Cleaner Production, 2023)

Transnational recycling of Australian export waste: An exploratory study - Linwei Du; Jian Zuo; Kyle O'Farrell; Ruidong Chang; George Zillante; Liancheng Li (Resources, Conservation and Recycling, 2023)

A supply chain allocation method for environmental responsibility based on fossil energy as the anchor for carbon responsibility - Chin Hao Chong; Yuan Gao; Linwei Ma; Zheng Li; Weidou Ni; Xiaoyong Zhou; Silvio Cristiano; Fanxin Meng; Wen Zhang; Ningyu Yan; Yan Hao; Gengyuan Liu (Journal of Cleaner Production, 2023)

Thallium release from biochar-amended soil to runoff in laboratory experiments - Lezhang Wei; Dafeng Cai; Fangqing Li; Yu Liu; Linwei Zeng; Dinggui Luo; Xuexia Huang; Tangfu Xiao; Hang Shi; Haiqi Yan (Environmental Pollution, 2023)

Distinguishing the main components of submarine groundwater and estimating the corresponding fluxes based on radium tracing method—taking the Maowei Sea for example - Linwei Li; Jinzhou Du; Xilong Wang; Yanling Lao (Acta Oceanologica Sinica, 2023)

An Interdecadal Change in the Influence of the NAO on Atlantic-Induced Arctic Daily Warming around the Mid-1980s - Cen Wang; Baohua Ren; Gen Li; Jianqiu Zheng; Linwei Jiang; Di Xu (Advances in Atmospheric Sciences, 2023)

Current investigation status of oxy-fuel circulating fluidized bed combustion - Ge Chen; Li Shiyuan; Wang Linwei (Fuel, 2023)

Landslide susceptibility mapping in Three Gorges Reservoir area based on GIS and boosting decision tree model - Fasheng Miao; Fancheng Zhao; Yiping Wu; Linwei Li; Ákos Török (Stochastic Environmental Research and Risk Assessment, 2023)

Enhancement in the thermoelectric performance of ZrNiSn-based alloys through extra Zr-rich nanoprecipitates with superstructures - Ruonan Min; Yinlu Gao; Xue Jiang; Xiong Yang; Linwei Li; Huijun Kang; Enyu Guo; Zongning Chen; Tongmin Wang (Chemical Engineering Journal, 2023)

Combing soil spatial variation and weakening of the groundwater fluctuation zone for the probabilistic stability analysis of a riverside landslide in the Three Gorges Reservoir area - Yang Xue; Fasheng Miao; Yiping Wu; Daniel Dias; Linwei Li (Landslides, 2023)

Slope Instability Analysis of the Qiongdongnan Basin in the Northern Part of the South China Sea: Implications for the Risk Evaluation of Deepwater Drilling - Linwei Ma; Shiguo Wu; Yanrui Liu; Jin Sun; Min Ouyang; Qingping Li; Yongpeng Qin; Dawei Wang (Journal of Ocean University of China, 2023)

Spatial and temporal distribution characteristics of pCO2 and CO2 evasion in karst rivers under the influence of urbanization - Kai Li; Xingxing Cao; Shiyu Zhou; Linwei Li (Environmental Science and Pollution Research, 2023)

The application of a homemade boomer source in offshore seismic survey: From field data acquisition to post-processing - Jianglong Zheng; Linwei Li; Jinxing Xie; Ting Yan; Biao Jiang; Xiaoxin Huang; Gege Hui; Tianguang Li; Mingming Wen; Yifan Huang (Journal of Applied Geophysics, 2023)

Effect of antifreeze protein on the quality and microstructure of frozen chicken breasts - Junlin Chen; Yaqi Fan; Xingguo Zhang; Zimeng Yuan; Hairu Zhang; Xinglian Xu; Jun Qi; Guoyuan Xiong; Lin Mei; Yuan Zhu; Linwei Yang; Chao Li (Food Chemistry, 2023)

Adaptive hybrid machine learning model for forecasting the step-like displacement of reservoir colluvial landslides: a case study in the three Gorges reservoir area, China - Li Linwei; Wu Yiping; Huang Yepiao; Li Bo; Miao Fasheng; Deng Ziqiang (Stochastic Environmental Research and Risk Assessment, 2023)

Experimental insights into the formation of secondary minerals in acid mine drainage-polluted karst rivers and their effects on element migration - Yeye Ren; Xingxing Cao; Pan Wu; Linwei Li (Science of The Total Environment, 2023)

Subsurface oxygen minima regulated by remineralization and bottom flushing along 123°E in the inner East China Sea - Bin Wang; Jianfang Chen; Haiyan Jin; Dewang Li; Shengquan Gao; Shichao Tian; Lin Sun; Haizhou Zhang; Linwei Li (Frontiers in Marine Science, 2023)
The summer hypoxia off the Changjiang Estuary is one of the largest coastal hypoxic systems in the world and has displayed spatial heterogeneity in recent years. Based on observation data in the summer of 2014, hypoxia was identified both in the bottom and mid-layers. Except for the typical bottom hypoxia in the submarine canyon, the subsurface oxygen minima (SOM) were captured in the mid-layer of 10~15 m, with lower dissolved oxygen in the mid-layer than at the bottom (30–50 m). This SOM phenomenon was located in the lower boundary of the pycnocline and above the Taiwan warm current (TWC) and Kuroshio subsurface water (KSSW). Due to the southern expansion of Changjiang diluted water (CDW), a high phytoplankton biomass (the maximum chlorophyll a of 25 μg L −1 , pH of 8.6, and DO of 11 mg L −1 ) band occupied the surface area along 123°E. By analyzing the 24-h continuous observation and high-resolution profile data, we revealed that the subsurface oxygen minima were predominantly controlled by remineralization and bottom-flushing effects. Fast local consumption occurred near the pycnocline layer, while the lateral transport of oxygen-rich ambient water replenished the bottom oxygen deficit from south to north. We summarize and contextualize three hot spots of hypoxia into a conceptual diagram and emphasize the influences of advection, mixing, and respiration on their location and severity. Overall, compared with the discussion about the low DO background of TWC/KSSW, this research highlights the flushing effects of TWC/KSSW that will reshape the hypoxia structure and alleviate the hypoxia severity in the south hypoxia area off the Changjiang Estuary.

Effectiveness of solid waste management policies in Australia: An Exploratory Study - Linwei Du; Jian Zuo; Ruidong Chang; George Zillante; Liancheng Li; Anthony Carbone (Environmental Impact Assessment Review, 2023)

Optimized Apriori algorithm for deformation response analysis of landslide hazards - Li Linwei; Wu Yiping; Huang Yepiao; Li Bo; Miao Fasheng; Deng Ziqiang (Computers & Geosciences, 2023)

Structural control on the Baiyinha'er gold mineralization (Southern Central Asian Orogenic belt) related to Early Paleozoic Paleo-Asian Oceanic subduction - Junlai Liu; Tao Jin; Yangwang Ou; Linwei Li; Cheng Zhang; Tianjiao Lu; Xiaoyu Chen (International Journal of Earth Sciences, 2022)

Alkalinity export to the ocean is a major carbon sequestration mechanism in a macrotidal saltmarsh - Yvonne Y.Y. Yau; Pei Xin; Xiaogang Chen; Lucheng Zhan; Mitchell Call; Stephen R. Conrad; Christian J. Sanders; Linwei Li; Jinzhou Du; Isaac R. Santos (Limnology and Oceanography, 2022)
Saltmarshes are a blue carbon ecosystem accumulating large quantities of organic carbon in sediments. Some of this carbon can be transformed into dissolved inorganic carbon (DIC) and methane (CH 4 ) that may eventually be exported to the ocean or atmosphere. Although extensive studies have quantified specific components of the carbon budget such as carbon burial, limited attention has been given to pore‐water‐derived carbon and total alkalinity (TA) exports to the ocean. Here, we quantified lateral exports to the ocean (outwelling) of 202 ± 160 and 78 ± 75 mmol m −2 d −1 of DIC and TA, respectively. The TA : DIC concentration ratio in the creek waters was ~ 1, implying TA production from anaerobic mineralization in sediments. The lateral TA exports were comparable to the local (94 ± 48 mmol m −2 d −1 ) and national (~ 50 mmol m −2 d −1 ) organic carbon burial. High TA exports could locally increase the ocean buffering capacity and contribute bicarbonate to the coastal ocean, acting as a long‐term carbon storage. Pore water traced by radon contributed 28–37% and 58–69% of DIC and TA exports. Separating the two major DIC components (i.e., CO 2 emissions and alkalinity exports) is essential to resolve the carbon sequestration potential from saltmarshes. Here, dissolved CO 2 emissions to the atmosphere accounted for 3–5% of total DIC outwelling. CH 4 emissions played a minor role offsetting around 0.3 to 6% of the carbon sequestration. Overall, we demonstrate that alkalinity export into the ocean can be an overlooked carbon sequestration pathway in saltmarshes at rates comparable to carbon burial.

Contrasting behaviors of 210Po, 210Pb and 234Th in the East China Sea during a severe red tide: Enhanced scavenging and promoted fractionation - Qiangqiang Zhong; Linwei Li; Viena Puigcorbé; Dekun Huang; Tao Yu; Jinzhou Du (Acta Oceanologica Sinica, 2022)

Estimating submarine groundwater discharge at a subtropical river estuary along the Beibu Gulf, China - Xilong Wang; Kaijun Su; Juan Du; Linwei Li; Yanling Lao; Guizhen Ning; Li Bin (Acta Oceanologica Sinica, 2021)

A hybrid interval displacement forecasting model for reservoir colluvial landslides with step-like deformation characteristics considering dynamic switching of deformation states - Linwei Li; Yiping Wu; Fasheng Miao; Yang Xue; Yepiao Huang (Stochastic Environmental Research and Risk Assessment, 2021)

Black phosphorus nanosheets and docetaxel micelles co-incorporated thermoreversible hydrogel for combination chemo-photodynamic therapy - Ruirui Li; Linwei Shan; Yanan Yao; Feifei Peng; Shanshan Jiang; Dandan Yang; Guixia Ling; Peng Zhang (Drug Delivery and Translational Research, 2021)

Effect of weakening of sliding zone soils in hydro-fluctuation belt on long-term reliability of reservoir landslides - Kang Liao; Yiping Wu; Fasheng Miao; Linwei Li; Yang Xue (Bulletin of Engineering Geology and the Environment, 2021)

Triggering factors and threshold analysis of baishuihe landslide based on the data mining methods - Fasheng Miao; Yiping Wu; Linwei Li; Kang Liao; Yang Xue (Natural Hazards, 2021)

Time-varying reliability analysis of Majiagou landslide based on weakening of hydro-fluctuation belt under wetting-drying cycles - Kang Liao; Yiping Wu; Fasheng Miao; Linwei Li; Yang Xue (Landslides, 2021)

Using a kernel extreme learning machine with grey wolf optimization to predict the displacement of step-like landslide - Kang Liao; Yiping Wu; Fasheng Miao; Linwei Li; Yang Xue (Bulletin of Engineering Geology and the Environment, 2020)

Effect of spatially variable saturated hydraulic conductivity with non-stationary characteristics on the stability of reservoir landslides - Yang Xue; Yiping Wu; Fasheng Miao; Linwei Li; Kang Liao; Guangzhao Ou (Stochastic Environmental Research and Risk Assessment, 2020)

Study of the Sensitive Properties of Marine Gas Hydrate Based on the Prestack Elastic Inversion - Siyou Tong; Jialin Wang; Linwei Li; Haiqi Zhang; Zhiqiang Wu; Yulan Shao (Journal of Ocean University of China, 2019)

Reverse-Time Migration of Converted S-Waves of Varying Densities - Siyou Tong; Ming Chen; Huawei Zhou; Linwei Li; Xiugang Xu; Zhiqiang Wu (Journal of Ocean University of China, 2019)

Risk assessment of snowmelt-induced landslides based on GIS and an effective snowmelt model - Fasheng Miao; Yiping Wu; Linwei Li; Kang Liao; Longfei Zhang (Natural Hazards, 2019)

A comparison of next-generation sequencing with clone sequencing in the diet analysis of Asian great bustard - Minghao Gong; Yu Ning; Morigen Han; Chenyang Zhao; Jingxing Tian; Linwei Li; Hongye Xiao; Gang Liu (Conservation Genetics Resources, 2019)

Bituminous coal combustion and Xuan Wei Lung cancer: a review of the epidemiology, intervention, carcinogens, and carcinogenesis - Jinhui Li; Jinjun Ran; Lung-chi Chen; Max Costa; Yunchao Huang; Xiao Chen; Linwei Tian (Archives of Toxicology, 2019)

Ionizing radiation exposure: hazards, prevention, and biomarker screening - Hongxiang Mu; Jing Sun; Linwei Li; Jie Yin; Nan Hu; Weichao Zhao; Dexin Ding; Lan Yi (Environmental Science and Pollution Research, 2018)

Using Mirror Migration of OBS Data to Image the Deepwater Area of South China Sea - Siyou Tong; Chuanxi Sun; Linwei Li; Dazhen Xu; Jie Wang (Journal of Earth Science, 2018)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Elements in Fine Particulate Matter (PM $$_{2.5}$$ 2.5 ) from Indoor Air During Household Stoves Coal Combustion at Xuanwei, China - K. H. Lui; C. S. Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Jinwen Li; Jun-Ji Cao; S. C. Lee; K. F. Ho (Aerosol Science and Engineering, 2017)

Evaluating the lingering effect of livestock grazing on functional potentials of microbial communities in Tibetan grassland soils - Mengmeng Wang; Shiping Wang; Linwei Wu; Depeng Xu; Qiaoyan Lin; Yigang Hu; Xiangzhen Li; Jizhong Zhou; Yunfeng Yang (Plant and Soil, 2016)

Proteomics analysis of liver tissues from C57BL/6J mice receiving low-dose 137Cs radiation - Lan Yi; Linwei Li; Jie Yin; Nan Hu; Guangyue Li; Dexin Ding (Environmental Science and Pollution Research, 2016)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.